Relation of the Prophet Muhammad (May Peace be Upon Him) with the Byzantines from the Revelation to the Trance of the Mu'ta (8 A.H. / 629 A.D) (Journal of the College of Education for Women, 2019)
Relations of the prophets Muhammad (May peace be upon him) with bygantlines from the revelation to the trance of al-hdybya 6 A.H/610 A.C.This research is concerned with Islamic historical events, particularly dunningthe time of the prophet Muhammad. It also explores relations of the apostle of godwith the rums and their allies the Arabs of Syria.During the first years of revelation Muslim had achieved great victoriesagainst the unbelievers. This accomplishm-ent had draw attention of some foreignforces such as the Arabs of Syria, who became snapicions of this new and activepower. Their hostile attend was demonstrated by striking an economical siege againstMuslims. They attacked the nabtins merchants whom used to provide the people ofmedina with their daily hiving like oil and flour, in the fifth year of al-hijra Muslimexpedition had undertaken against the Arabs of Syria, which was known as Dwamatol-Iandal. Islamic historical sources have conidial it to be the first expedition ofMuhammad against the Rums.Actually this period is quite different from coming years because struggle inearly stages was, in fact, between Muslims and Arab of Syria (Iakham, iutham andKalb tribes) while in hirer period Islamic tropes had to face the roman forces themselves.Accordingly, Success in Dimwit of. Iandal was tremendously fruitful andeffective at the same him exactly as prophet had planed. His main goal was to stringthen a brotherly relation among Muslim society, a view that had a long strategicdistance and was to be the first brick in establishing the glorious state of Islam.Finally, interest of the Apostle of god in northern tribes had continued evenafter conquering Mecca.Many records mentioned that Muhammad (May peace be upon him) had anexpeditionheaded by zayad b.usam, before his death.